Interfacial-assembly engineering of asymmetric magnetic-mesoporous organosilica nanocomposites with tunable architectures. Issue 42 (17th October 2022) - Wu, Yue; Sun, Yangyi; Zhang, Chengyu; He, Mengyao; Qi, Dongming
Abstract : Interfacial-assembly engineering for controllable preparation of length-tunable asymmetric nanoarchitectures ( i.e., organosilica nano-tails) on magnetic Fe3O4 nanoparticles. Abstract : The asymmetric morphology of nanomaterials plays a crucial role in regulating their physical and chemical properties, which can be tuned by two key factors: (i) interfacial interaction between seed particles and growth materials (anisotropic island nucleation) and (ii) reaction kinetics of the growth material (growth approach). However, controllable preparation of asymmetric nanoarchitectures is a daunting challenge because it is difficult to tune the interfacial energy profile of a nanoparticle. Here, we report an interfacial-assembly strategy that makes use of different surfactant/organosilica-oligomer micelles to actively regulate interfacial energy profiles, thus enabling controllable preparation of well-defined asymmetric nanoarchitectures ( i.e., organosilica nano-tails) on magnetic Fe3 O4 nanoparticles. For our magnetic nanocomposite system, the assembly structure of surfactant/organosilica-oligomer micelles and the interfacial electrostatic interaction are found to play critical roles in controlling the nucleation and architectures of asymmetric magnetic-mesoporous organosilica nanocomposite particles (AMMO-NCPs). Surfactant/organosilica-oligomer micelles with a one-dimensional wormlike linear structure could strengthen the interfacial assembly behavior between seed particles and growth materials, and thus achieved the longest tail length (25 μm) exceeding the previously reported highest recorded value (2.5 μm) of one order of magnitude. In addition, clickable AMMO-NCPs can employ a thiol–ene click reaction to modify their surface with a broad range of functional groups, such as amines, carboxyls, and even long alkyl chains, which allows for expanding functionalities. We demonstrate that C18 alkyl-grafted AMMO-NCPs can self-assemble into self-standing membranes with robust superhydrophobicity. In addition, carboxyl-modified AMMO-NCPs exhibit excellent adsorption capacity for cationic compounds. This study paves the way for designing and synthesizing asymmetric nanomaterials, which possess immense potential for future engineering applications in nanomaterial assembly, nanoreactors, biosensing, drug delivery, and beyond.